"Oh, older people, it's boring": Nurse academics' reflections on the challenges in teaching older person's care in Australian undergraduate nursing curricula. Issue 1 (February 2023) - Rayner, Jo-Anne; Fetherstonhaugh, Deirdre; Beattie, Elizabeth; Harrington, Ann; Jeon, Yun-Hee; Moyle, Wendy; Parker, Deborah
ABSTRACT: Background: Nursing students encounter older people in all health care sectors; however, few choose a career primarily focused on older person's care. Aim: To explore the challenges to teaching older person's care to Bachelor of Nursing students and how pre-registration nursing students are prepared to care for older people, part of a large study investigating content on care of older people in Australian nursing curricula. Methods: A purposive sample of Australian nurse academics involved in Bachelor of Nursing curriculum development or delivery completed a telephone-assisted survey. Qualitative content analysis of two open-ended questions was undertaken. Results: All Australian schools of nursing participated, and 45 nurse academics were interviewed. Reflecting on the challenges of teaching older person's care to nursing students, most participants felt the curriculum was too crowded and some called for a 4 year degree. In addition, students' ageist attitudes, fuelled by unrealistic portrayals of nursing in popular culture, were reinforced by curricula being acute care focused and the ageist attitudes of some nurse academics. Conclusions: Teaching older person's care in Australian nursing curricula is challenged by insufficient time and ageism among students and academics. Regulatory bodies need to urgently provide direction so that nursing curricula content aligns with emerging Australian health care priorities, in particular the health care needs of older people.